Histopathological Study of Mastacembelus armatus (Lecepede, 1800) Infected with Tapeworm from Osmanabad district (M.S.) India - Ram Chavan, Jaywant Dhole, Dinkar Tambe and (Recent Research in Science and Technology, 2011)
The freshwater fish Mastacembalus armatus (Lecepede, 1800) collected from Osmanabad district during the period of June 2008 and after dissection their intestinal passage was examined for tapeworm parasites. The tapeworm, Circumoncobothrium sp. Shinde (1968) was recovered from intestine Ophalocephalus leucopunctatus. The histopathological studies were carried outÃ‚Â and observations clearly shows that the parasites, Circumoncobothrium sp. was approaching to the intestinal villi, embedded in the fibroblast cell, plasma cell and are attached to the intestinal villi. The histopathological studies of tapeworm Circumoncobothrium sp. have been studied to find the pathological changes and extent of damage of the intestinal layers of M. armatus.